PENDAMPINGAN PENGGUNAAN MEDIA UNTUK MENINGKATKAN KREATIVITAS ANAK MELALUI METODE BERMAIN PLASTISIN USIA 5-6 TAHUN DI TKK NEGERI NASARET WERE - Yunita, Antonia; Maku, Karmelia Rosfinda Meo; Tarung, Maria Febriani; Meo , Benedikta Indryani (Jurnal Citra Magang dan Persekolahan, 2024)
Plasticine media can help increase children's creativity in recognizing and using plasticine media in activities or learning processes in class. This research aims to determine the use of plasticine media in improving children's creative abilities at the Nasaret State Kindergarten. The research method used is descriptive qualitative method. The subjects in this research were teachers and children from group B with a total of 12 people consisting of 5 women and 7 men. Data collection techniques are carried out through observation, interviews and documentation. The research results achieved after using plasticine media in the learning process showed that there was an increase in children's creativity in developing. Through this, researchers see that children can develop their thinking abilities, children can also solve simple problems they face, this reflects that the children of TKK Negeri Nasaret Were are very creative in various things.